State ownership effect on firms' FDI ownership decisions under institutional pressure: a study of Chinese outward-investing firms - Cui, Lin; Jiang, Fuming (Journal of International Business Studies, 2012)
This study investigates the effect of state ownership on Chinese firms’ foreign direct investment (FDI) ownership decisions. It adopts a political perspective to extend the application of institutional theory in international business research. Specifically, it examines firms’ heterogeneous responses to external institutional processes during foreign market entry, while taking into consideration the political affiliation of firms with the external institutions. We argue that state ownership creates the political affiliation of a firm with its home-country government, which increases the firm's resource dependence on home-country institutions, while at the same time influencing its image as perceived by host-country institutional constituents. Such resource dependence and political perception increase firms’ tendency to conform to, rather than resist, isomorphic institutional pressures. We tested our hypotheses using primary data for 132 FDI entries made by Chinese firms during 2000–2006, and we found that the effects of home regulatory, host regulatory and host normative pressures on a firm to choose a joint ownership structure were stronger when the share of equity held by state entities in the firm was high.